Validation of the Chinese Version of the Multidimensional Workaholism Scale. (November 2021) - Xu, Yan; Li, Chaoping
The aim of this study was to translate the Multidimensional Workaholism Scale (MWS) into Chinese and then test its reliability and validity among full-time Chinese employees in two stages. In Study 1 ( N = 220), the MWS was translated and exploratory factor analysis was conducted resulting in a four-factor solution consistent with the original MWS: motivational, cognitive, emotional, and behavioral. In Study 2 ( N = 425), confirmatory factor analysis showed that a four-factor, bifactor model was the best fit for the data. Configural, metric, and scalar invariance models were tested which demonstrated that the Chinese version of the MWS did not differ across gender, age, and job position groups. Finally, workaholism and engagement were related and distinct from one another, and they correlated with emotional exhaustion, work-family conflict and life well-being uniquely. This study indicated that the Chinese version of the MWS is a valid and reliable tool for Chinese employees, and this has important practical implications for the individual health and career development of Chinese working adults.